Coherence between geodetic and seismic deformation in a context of slow tectonic activity (SW Alps, France). (April 2015) - Walpersdorf, A.; Sue, C.; Baize, S.; Cotte, N.; Bascou, P.; Beauval, C.; Collard, P.; Daniel, G.; Dyer, H.; Grasso, J.-R.; Hautecoeur, O.; Helmstetter, A.; et al.
Graphical abstract: Highlights: 15 years of dense GPS measurements converge to sub-millimetric rates per year. Geodetic and seismic deformation coherent in amplitude and direction. Both plate tectonics and buoyancy forces needed to explain uplift and extension. Abstract: A dense, local network of 30 geodetic markers covering a 50 × 60 km 2 area in the southwestern European Alps (Briançon region) has been temporarily surveyed in 1996, 2006 and 2011 by GPS. The aim is to measure the current deformation in this seismically active area. The study zone is characterized by a majority of extensional and dextral focal mechanisms, along north–south to N160 oriented faults. The combined analysis of the three measurement campaigns over 15 years and up to 16 years of permanent GPS data from the French RENAG network now enables to assess horizontal velocities below 1 mm/year within the local network. The long observation interval and the redundancy of the dense campaign network measurement help to constrain a significant local deformation pattern in the Briançon region, yielding an average E–W extension of 16 ± 11 nanostrain/year. We compare the geodetic deformation field to the seismic deformation rate cumulated over 37 years, and obtain good coherencies both in amplitude and direction. Moreover, the horizontal deformation localized in the Briançon region represents a major part of the Adriatic-European relative plate motion. However, the average uplift of the network in an extensional setting needs the presence of buoyancy forces in addition to plate tectonics.